How do digital capabilities affect firm performance? The mediating role of technological capabilities in the "new normal" - Jorge Heredia; Mauricio Castillo-Vergara; Cristian Geldes; Felix M. Carbajal Gamarra; Alejandro Flores; Walter Heredia (Journal of Innovation & Knowledge (JIK), 2022)
This study proposes a model to explain the effect of digital capabilities on firm performance in the "new normal" context from a firm-level perspective. Moreover, it analyzes the mediating role of technological capabilities and the Human Development Index (HDI) in explaining firm performance. Our study used data from the World Bank's Enterprise Surveys 2020, which included 999 firms from 27 countries. We applied the methodological approach, partial least square structural equation modeling (PLS-SEM), to test the hypothetical model. The results show that digital capabilities positively influence firm performance only through technological capabilities. We also empirically demonstrate that digital skills in low HDI economies have a more significant indirect effect on firm performance than in high HDI countries. Finally, some promising avenues for future research and implications for managers and policymakers are suggested based on these findings.
Keywords: 650; COVID-19; Digital capabilities; Firm performance; human development index (HDI); PLS-SEM; Technological capabilities